REINSURANCE IN AN INNOVATION ECONOMY (Marketing Journal, 2025)
The article scientifically analyzed the strategies and priority directions for the development of reinsurance institutions in the context of an innovative economy. During the study, the role of reinsurance mechanisms in risk diversification, improving capital efficiency, and strengthening the financial stability of insurance companies was substantiated. In addition, the dynamics of reinsurance volumes in general insurance and life insurance sectors were assessed, which revealed the need for innovative appro aches. The study identified digital transformation, coverage of new types of risks, international cooperation, and the integration of ESG principles as key factors ensuring the long -term development of reinsurance institutions. The obtained results demonst rated the potential for sustainable development of the national insurance market and its alignment with international standards.
Keywords: reinsurance; innovative economy; insurance company; risk management; financial stability; capital efficiency; digital transformation; ESG integration; insurance portfolio; retrocession